1885 Ill. Laws 57 - (:unkn) unknown (My University, 1885)
An Act to Protect Cemeteries and to Provide for their Regulation and Management, § 1: Prohibited destroying, mutilating, or injuring any tomb, monument, stone, vault, tree, shrub, or ornament, or any object whatsoever in any cemetary. Also prohibited hunting, shooting, or discharging any gun, pistol, or other missile within any cemetary limits.
Keywords: DISCHARGE; HUNTING REGULATION